Focal bone defects in type 2 diabetes mellitus patients with acute hip fractures - Yuan, Yi; Zhang, Rui; Yang, Minghui; Xia, Wei; Su, Yongbin; Jian, Junming; Liu, Yandong; Guo, Zhe; Zhao, Xingyu; Zhu, Shiwen; Cheng, Xiaoguang; Wu, Xinbao; et al. (Quantitative Imaging in Medicine and Surgery, 2025)
Background: Osteoporotic hip fractures are associated with low bone strength, which is usually explained by low bone mineral density (BMD). However, even though type 2 diabetes mellitus (T2DM) participants have an increased incidence of osteoporotic hip fractures, paradoxically, there is increasing evidence indicating that T2DM patients have higher BMD than those without T2DM. The detection of focal osteoporosis could help us understand the bone quality of the proximal femur in participants with and without T2DM. This study aims to investigate whether focal bone defects are associated with hip fracture in those with and without T2DM by using statistical atlases. Methods: Four hundred and nineteen low-energy acute hip fracture cases and 288 controls with hip computed tomography (CT) scans were included in the case-control study. Differences in the spatial distributions of volumetric bone mineral density (vBMD), cortical bone thickness, cortical vBMD, and vBMD in a layer adjacent to the endosteal surface were investigated using voxel-based morphometry (VBM) and surface-based statistical parametric mapping (SPM). Results: For both with and without T2DM groups, there is a clear bone defect at the femoral neck and intertrochanteric region in cortical thickness variables for cases. The endocortical trabecular bone mineral density (ECTD) and vBMD distributions show quite dramatic differences between fractures and controls in both with and without T2DM groups. In particular, in the women’s comparison results, the significantly different region between cases and controls in the T2DM cohort was larger than that in the without T2DM cohort. After adjustment for the covariates of age, height, and weight, the risk of hip fracture among people with diabetes was higher overall than among participants without diabetes, in both men and women. The spatial distribution of trabecular vBMD and focal areas of endocortical bone defect both result in an increased risk of hip fracture in T2DM patients. Conclusions: The spatial distribution of trabecular vBMD and focal areas of endocortical bone defect both result in increased risk of hip fracture in T2DM patients.
CRIS-Team Scopus Importer:2025-10-17
Keywords: Acute hip fracture; bone mineral density (BMD); statistical parametric mapping (SPM); type 2 diabetes mellitus (T2DM); voxel-based morphometry (VBM)